2004
DOI: 10.1021/np0498713
|View full text |Cite
|
Sign up to set email alerts
|

Ingenamine G and Cyclostellettamines G−I, K, and L from the New Brazilian Species of Marine SpongePachychalinasp.

Abstract: The chemical investigation of the cytotoxic and antituberculosis active MeOH crude extract of the marine sponge Pachychalina sp. led to the isolation of six new nitrogenous metabolites, including ingenamine G (1), as well as a mixture of new cyclostellettamines G, H, I, K, and L (10-14) with the known cyclostellettamines A-F (4-9). Structural assignments of compound 1 were based on the analysis of MS and NMR data, while the structures of compounds 10-14 could be established by HPLC-MS/MS analysis. Ingenamine G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 28 publications
1
51
0
3
Order By: Relevance
“…Ingenamine G (89) displayed cytotoxic activity against HCT-8 (colon), B16 (leukemia) and MCF-7 (breast) at 8.6, 9.8 and 11.3 µg mL -1 , respectively. 51 Investigation on the cytotoxic mechanismof-action of compound 89 indicated that it promotes DNA-damage, especially in S-phase of the cell-cycle. The n-BuOH extract of P. alcaloidifera yielded a mixture of eleven 3-alkylpyridine compounds, cyclostellettamines A-I, K and L (90-100), among which alkaloids 96-100 are new representatives of this class.…”
Section: Marine Spongesmentioning
confidence: 99%
“…Ingenamine G (89) displayed cytotoxic activity against HCT-8 (colon), B16 (leukemia) and MCF-7 (breast) at 8.6, 9.8 and 11.3 µg mL -1 , respectively. 51 Investigation on the cytotoxic mechanismof-action of compound 89 indicated that it promotes DNA-damage, especially in S-phase of the cell-cycle. The n-BuOH extract of P. alcaloidifera yielded a mixture of eleven 3-alkylpyridine compounds, cyclostellettamines A-I, K and L (90-100), among which alkaloids 96-100 are new representatives of this class.…”
Section: Marine Spongesmentioning
confidence: 99%
“…Fontana and co-workers were able to feed the mollusc Haminoea orbignyana with radio-labelled [2-14 C]-acetic acid and nicotinic acid-carboxy- 14 C. After injection of the labeled precursors they detected significant levels of radioactivity in the isolated haminol-2 (1.69). They also administered to the mollusc d 4 .…”
Section: Haminol -2 (169) Is a 3-alkylpyridine Alkaloid Isolated Fromentioning
confidence: 99%
“…A fração Dv-hex-5B (0,011 g) apresentou composto majoritário ainda impuro, e foi purificada por CLAE (coluna: Waters m-Porasil sílica gel 5 mm, 19 x 300 mm; eluente: n-hexano/AcOEt/MeOH 80:18:2; fluxo: 1 mL/min; detecção: UV l max 254 nm). Obteve-se 1,4 mg da lactona da furodisinina (14). 40 As outras frações obtidas do extrato hexânico apresentaram somente esteróis, esteroides, ésteres do glicerol e ácidos graxos e não foram investigadas.…”
Section: Estudo Químico Da Esponja Dysidea Spunclassified
“…por partição líquido-líquido e por uma série de separações cromatográficas (ver Parte Experimental) levou ao isolamento da lactona da furodisinina (14) e ao esterol 9a,11a-epoxicolest-7-eno-3b,5a,6a,10-tetrol-6-acetato (15). A lactona da furodisinina 14 foi originalmente isolada da esponja Dysidea etheria.…”
unclassified
See 1 more Smart Citation